Dehumanisation Of Moronene Hukaea Laea Indigenous Community In Setting The Boundary Of Ulayat Rights - Andi Yaqub; Ashadi L. Diab; Andi Novita Mudriani Djaoe; Riadin Riadin; Iswandi Iswandi (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
The determination of the area of customary rights of indigenous peoples is a form of protection for indigenous peoples, a step to overcome vertical conflicts between the Moronene Hukaea Laea indigenous people and conservation or national park managers. This study aims to capture the extent to which the position and existence of Perda no. 4 of 2015 on the recognition of the customary rights of the moronene indigenous people of Hukaea Laea. This type of research is descriptive analysis with a qualitative approach, the research location is in Watu-Watu Village, Lantari Jaya District and Rawa Aopa Watumohai National Park, Bombana Regency and the data collection of this study is through direct interviews and deductive conclusions are drawn. Based on the results of this study, the forms of dehumanization of the Moronene Hukaea Laea indigenous people include: (1) In 1997 the Moronene Hukaea Laea indigenous people experienced intimidation by the universe broom group such as burning houses and land and in 2002 repeated home destruction and eviction ulayat areas by the government because the Moronene indigenous people are in conservation areas or national parks, the pretext of expulsion and arrest of customary leaders and indigenous peoples of Moronene Hukaea Laea has based on a negative stigma that the existence of indigenous peoples is a group that destroys ecosystems and ecology. (2) In 2015 the stipulation of Regional Regulation No. 4 of 2015 is not substantive because it only regulates the existence of indigenous peoples, not the absolute determination of territory by the Hukaea Laea indigenous people. This is indicated by the policy of the Minister of Forestry which concluded that based on the total population of the Hukaea Laea Indigenous Peoples, only 6,000 hectares could be controlled. Based on this policy, the local government shows inconsistency towards the indigenous Moronene Hukaea Laea after placing its position as a mediator between the Minister of Forestry, conservation area managers, and the Hukaea Laea Indigenous Community.